Association between metacognitive listening strategy use and listening comprehension ability and problems among Malaysian ESL students - Sadatmir, Seyedehsima (2018)
Listening comprehension is a fundamental part of both L1 and L2 communication. Although the number of research on different aspects of L2 listening comprehension has increased, there are still many other aspects that can be discovered about listening comprehension. One of the most problematic issues in research on listening comprehension is that the performance of the learner mostly includes mental procedures that are not directly noticeable. This research seeks to identify and describe the association of metacognitive listening strategy use of ESL students with different listening comprehension ability levels and comprehension problems based on the theory of cognitive process of listening. Both quantitative and qualitative methods were used in this research. The Listening section of International English Language Testing System (IELTS) was conducted to identify listening comprehension ability levels among 135 ESL students. Two adapted questionnaires, the Listening Comprehension Problem Questionnaire (LCPQ) and the Metacognitive Listening Strategy Questionnaire (MLSQ), were also distributed to the participants after completing the test in order to examine their perceived listening comprehension problems and metacognitive listening strategy use. The Think- Aloud (TA) method was used in this research in order to identify the types, frequency and patterns of metacognitive listening strategy use. Six cases were selected purposively from the participants in two groups of skilled and less- skilled listeners. They underwent TA procedures after TA training to expose the way they apply metacognitive listening strategies while doing a listening task. Verbal protocols obtained from the TA procedure were transcribed and analysed both quantitatively and qualitatively. The results revealed more frequent use of metacognitive listening strategies by the skilled listeners. Subsequently, the qualitative results exposed the linear sequence of Metacognitive Listening Strategy Use (MLSU) for all cases. This result showed the skilled cases applied linear patterns more than the less- skilled peers although there were some recursive moves in each pattern. This finding can be an effective start in visualizing and examining patterns of MLSU which is absent in the literature in a variety of contexts. Moreover, TA procedure can be used as a dynamic methodology for investigating how to use strategies in EFL/ ESL teaching and learning.